Powerful play: using educational toys in the Iqra' learning method for preschoolers / Asrol Hasan - Hasan, Asrol (2006)
Preschool education is one of the institutions which functions as a way to improve and further develop the understandings in all aspects of development for children aged 4 to 6 years old. Basic Qur'an education is one of the aspects which is included in the Islamic education curriculum, set up by the Malaysian Ministry of Education Curriculum Development Centre. Iqra' is one of the faster learning methods which has been used in Malaysia since 1995 and at one time was introduced at primary school stage for year one students. Now the Iqra' method is being used widely in most preschools in Malaysia, primarily by private preschools. The method of learning through playing is one the approaches which is given priority by the Malaysian Ministry ofEducation for use in· preschool education. The researcher believes that incorporating this approach with Iqra' method into topics such as basic knowledge of the Qur'an will not only enhance the learning process but also make it more enjoyable, hence increasing the students appreciation of the importance of the Qur'an and its benefits which is important for the children, as Muslims. At the age group of 4 to 6 years old, it is very difficult for these children to understand only by using books. Therefore there is a room for improvement in the methodology. An educational toys were designed based on the Iqra' method from Iqra' Book One. The Iqra' toy was tested and evaluated in two selected private preschools in the Klang Valley area. The purpose of this study was to find whether preschoolers between 4 to 6 years old gain a better understanding of basic Qur'an through Iqra' method if they are required to play with an educational toys rather than if they only attend the conventional Qur'an class. The test was conducted on 40 subjects, while 20 subjects were exposed to the conventional method. Three types of evaluation were used to evaluate these students which are: pre-test, post-test (summative) and a formative evaluation. The results of the tests showed that both experimental groups at two selected preschools showed an increase of 22.5% to 34% performance on the post-test, compared to the pre-test, after using the Iqra' Educational Toy as a learning aid. It was also found that the children aged 4 years old showed a better performance compared to children aged 5 years old. The teachers agreed that this method was 90% successful and it was more enjoyable than learning through books or by the conventional method they were used to. A ~ajor recommendation was that toys and this method can be used broadly on all types of preschools in Malaysia and that more research should be conducted on the method of learning through playing at higher levels, such as primary school, secondary school or University level. As an early recommendation, it is hoped that the Ministry of Education can integrate the method as a part of the preschool curriculum as one of the approaches that can be used primarily at government preschools. This research focused on two concepts of toys in general and it is hoped that in the future, this concept toy will become more interesting with the addition of technology like sound effects or graphic animations.